Perceptions of Teacher Communication Styles in Managing Classroom Behavior in Australian High Schools - Anggi Moannissa (Green Publisher Indonesia, 2025)
This qualitative study examines Australian high school students’ perceptions of teacher communication styles in classroom behavior management. While disciplinary practices are often analyzed from institutional perspectives, this research prioritizes student voices to explore how communication is experienced, interpreted, and shapes classroom dynamics. Semi-structured interviews with Year 10 to Year 12 students across three diverse schools revealed key themes related to fairness, empathy, and emotional impact. Findings indicate that students respond more favorably to communication that balances authority with respect and clarity with compassion. Negative reactions—such as disengagement or resistance—often arose from communication perceived as harsh, public, or demeaning. Conversely, calm and respectful interactions fostered trust and engagement. The study underscores the significance of relational communication in behavior management, suggesting that effective discipline is not just procedural but fundamentally interpersonal. These insights offer valuable implications for teacher training, advocating for strategies that uphold student dignity while cultivating positive classroom environments.